THE ROLE OF MODEL BILATERAL INVESTMENT TREATIES (MODEL BITS) IN THE IMPLEMENTATION OF A SUSTAINABLE INVESTMENT POLICY - Ergashboyev , Mardonbek (Zamonaviy ilmiy yondashuvlar va texnologik taraqqiyotning ustuvor yo‘nalishlari, 2026)
This thesis analyzes the role of model bilateral investment treaties (Model BITs) and their importance in the negotiation and adoption of bilateral treaties. The significance of model BITs in harmonizing investment policy and ensuring a stable environment for investors is illustrated by the examples of the BIT programs in Germany and the USA, countries with extensive practical experience in this area. In the conclusion, the author’s personal views are presented regarding the importance and necessity of developing a Model BIT for Uzbekistan.